Establishing the optimal essential amino acid ratios in juveniles of Nile tilapia (Oreochromis niloticus) by the deletion method - Diogenes, A. F. [UNESP]; Fernandes, J. B. K. [UNESP]; Dorigam, J. C. P. [UNESP]; Sakomura, N. K. [UNESP]; Rodrigues, F. H. F. [UNESP]; Lima, B. T. M. [UNESP]; Goncalves, F. H. [UNESP] (Wiley-Blackwell, 2016)
One of the strategies used to improve fish production is lowering the feed costs and the environmental impact by reducing dietary protein content. Using the deletion method, we determined the optimal amino acid (AA) ratio for Nile tilapia (Oreochromis niloticus) (body weight 20g). Eleven experimental diets and four replications, taken two at a time, distributed in a randomized block design were used. For this trial, a balanced diet (BD) was formulated. Ten other diets were formulated by the deletion method, in which the BD diet was adjusted to result in a reduction of 45% of the test amino acid. Fish were fed three times a day for 57days. Groups of fish at the beginning and at the end of the experiment were euthanized for further determination of the carcass nitrogen (N) composition. The optimal ratio of each AA was derived by dividing the requirement for each AA by the requirements for lysine. The essential AA ratios, expressed relative to lysine (=100), were methionine 64, threonine 93, tryptophan 24, arginine 125, histidine 34, isoleucine 57, leucine 96, valine 76 and phenylalanine 101. Our findings might be used to design strategies aimed at reducing the production costs of Oreochromis niloticus.
Keywords: amino acid; deletion method; nitrogen retention; nutrition; protein; tilapia